Children's Legal Competence in Electronic Transactions: An Analysis of Normative Gaps from the Perspective of Indonesian Civil Law - Aina Tasya Maharani Samaila; Muh Arfandi; Andi Azka Azkia Laelita Harun; Andi Faizah Aulia Putri; Agung Darwis; Cahaya Amanda Azis; St Alifyani Zahra (Civiliza Publishing, 2026)
The rapid technological developments in the current era are also changing various types of human interactions, one of which is economic interaction. Nowadays, many things can be searched for and purchased online or through fully digital e-commerce platforms. This phenomenon cannot be separated from the active role of minors in online transactions. However, the involvement of children in this digital pattern has particular urgency in civil law, related to the legal capacity of a child in the context of making agreements. Based on Articles 1320 and 1330 of the Civil Code, children who have not reached adulthood do not have the capacity to independently make valid agreements. Research results indicate a normative gap (recht vacuum) in the Electronic Information and Transactions Law (UU ITE), which has not specifically regulated the minimum age and legal capacity regarding subjects in electronic transaction phenomena. Thus, transactions carried out by minors can be canceled due to the failure to meet the subjective requirements. And if a dispute occurs, it will be borne or transferred to the parents or guardians as the responsible party. This research provides the idea for the need to upgrade regulations regarding strong money and be stricter to provide legal certainty and protection for children, business actors, as well as digital platform organizers.